A dual-channel responsive near-infrared fluorescent probe for multicolour imaging of cysteine in living cells. Issue 19 (27th April 2017) - Ye, Zhuo; Duan, Chong; Hu, Qiao; Zhang, Yue; Qin, Caiqin; Zeng, Lintao
Abstract : Aberrant levels of cysteine (Cys) in living cells are closely related to some diseases; thus in situ visualization of intracellular Cys is very helpful for the investigation of physiological and pathological processes. Abstract : Aberrant levels of cysteine (Cys) in living cells are closely related to some diseases; thus in situ visualization of intracellular Cys is very helpful for the investigation of physiological and pathological processes. Herein, we report a dual-channel responsive near-infrared (NIR) fluorescent probe for multicolour imaging of Cys in living cells. The probe was constructed with a NIR BODIPY attached to 7-nitrobenzofurazan (NBD) via an ether bond. Upon substitution of the ether with the nucleophilic thiolate of Cys, a NIR BODIPY fluorophore was released to produce a significant fluorescence-enhanced signal at 735 nm. Moreover, Cys induced an intramolecular rearrangement reaction on the electrophilic site of NBD, resulting in another emission band at 540 nm. This probe exhibited some favorable properties including a dual-channel response, high fluorescence brightness, good photostability, fast response, low detection limit (22 nM) and low cytotoxicity. Furthermore, the probe was successfully applied for multicolour imaging of Cys in living cells.